Multi-omics analysis and evidence of IL1R1 as a potential biomarker for diabetes-associated intervertebral disc degeneration - Yi, Meng; Lin, Wancheng; Liu, Shijie; Zhang, Yao; Song, Jipeng; Yin, Yukun; Ding, Lixiang (Frontiers in Immunology, 2025)
IntroductionLow back pain (LBP), primarily driven by intervertebral disc degeneration (IDD), imposes a significant global health burden. While type 2 diabetes mellitus (T2DM) is a recognized risk factor for IDD, the shared molecular mechanisms remain incompletely characterized.MethodsThis study employed integrated bioinformatics (WGCNA, machine learning - LASSO, RF, ANN) on human T2DM and IDD transcriptomic datasets, alongside scRNA-seq analysis of diabetic mouse nucleus pulposus (NP) tissue, to identify key drivers of diabetes-associated IDD.ResultsBioinformatics analysis of human data identified three diagnostic biomarkers (S100A12, IL1R1, FCGR2B) and constructed a robust ANN diagnostic model (AUCs: 0.744-0.868). IL1R1 emerged as the most significant risk factor. scRNA-seq revealed altered cellular composition in diabetic discs, notably increased proportion of granulocytes (predominantly neutrophils) and decreased proportion of nucleus pulposus (NP) cells. IL1R1 was highly expressed in specific diabetes-associated NP subpopulations and showed significant positive correlation with neutrophil infiltration. Functional enrichment linked IL1R1 to inflammation, DNA repair, and immune pathways. Furthermore, we constructed a regulatory network (STAT1/STAT6-IL1R1-miRNAs-lncRNAs) and identified icariin as a potential therapeutic candidate via molecular docking.DiscussionThese findings establish IL1R1 as a pivotal molecular bridge connecting T2DM and IDD, driven by neutrophil-mediated inflammation and NP cell dysfunction, offering novel diagnostic and therapeutic avenues.